Students’ Response Towards the Improvement of Reading Comprehension Through Herringbone Technique - Opik Dwi Indah; Muhammad Affan Ramadhana (South Sulawesi Education Develoment (SSED), 2020)
This research aimed to find out how students’ response after they learned reading to improve their comprehension skill through herringbone technique. Descriptive quantitave method was used in this research. It aimed at finding out and describing students’ response towards the improvement of reading comprehension through herringbone technique.The subject of the research was the fourth semester students in Academic year 2019/2020. The researchers applied purposive sampling technique and took class C from three classes. The total sample of this research was 38 students. In collecting the data, the researchers used a questionnaire to gain students’ response. Total number of questionnaires were 10 numbers with positive statements. The result shows there were 35 students (92.11%) who responded strongly agree and 3 students (7.89%) who responded agree. It means that all students gave good response for this technique. Based on the result of this research, the researchers can conclude that herringbone technique is a good technique to be applied in comprehending a reading text because this method used 5W+1H questions as guidance for the reader to comprehend the content of a reading text.